Implementasi Program Deradikalisasi Terorisme oleh Badan Nasional Penanggulangan Terorisme (BNPT): Sebuah Perspektif Political Spectrum - Zuhri, Saefudin (IAIN Surakarta, 2018)
Terrorism is a serious problem for the world recently. The groups of terror currently appeared to be closely related to groups that have radical understanding. They claim that their actions are the implementation of Jihaad. The goal of their struggle is to establish the Khilafah Islamiyah, a global leadership system based on Islamic law. Countries embraced nation state, including Indonesia, labeled them as a radical group-terrorism. The Government of Indonesia through the National Agency for Combating Terrorism (BNPT) has a special strategy to combat radical-terrorism groups with the policy of de-radicalization. De-radicalization attempts to reduce and eliminate one's radical understanding. This study will discuss de-radicalization in the political Spectrum perspective. This paper specifically takes a study on the concept and implementation of de-radicalization programs implemented by the National Agency for Counter-Terrorism (BNPT) during this time. This paper shows an answer whether the deradicalization efforts undertaken by BNPT will change the political spectrum of a person.